PEMANFAATAN METODE CERBER UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS: DOI: https://doi.org/10.37850/cendekia.v12i1.81 - Pi’i Susanto (Fakultas Agama Islam Universitas Billfath, 2020)
This research is aligned with the wishes of researchers to: 1) Develop a Cerber Method (Continuous Story) to increase the activities of students of Social Sciences Subjects in Class IX A Students of SMP Negeri 1 Sekaran 2018/2019 Academic Year. (2) Knowing the Cerber Method (Continuous Story) can improve Student Learning Outcomes Achievement in Social Studies Subjects in Class IX A Students of SMP Negeri 1 Sekaran 2018/2019 Academic Year. The activeness of students in asking from 30.43% in cycle 1 to 91.30% in cycle 2. The activeness of students in answering the original question 26.09% in cycle 1 to 86.96% in cycle 2. The activeness of students in expressing their original opinion was 30.43% in cycle 1 became 78.26% in cycle 2, so did the percentage of mastery learning 78.26% to 95.65% in cycle 2, the average grade of grade IX A was 75.00 in cycle 1 being the average grade of grade IX A was 94, 00 in cycle 2. The activeness of students also seems to be very enthusiastic in completing assignments given to students showing improvement from cycle I to Cycle II. From the results of interviews with students about the learning process that has been going on, the results are the same as in cycle 1, where all students express very happy. Thus, after analyzing the results of the second cycle, it was decided not to proceed to the next cycle because this research was considered complete. From the results of the analysis of the learning process carried out in cycle 1 and cycle 2 it can be concluded that the Cerber Method (Continuous Story) can increase the activity of Social Studies Subjects in Class IX A Students of SMP Negeri 1 Sekaran 2018/2019 Academic Year. The Cerber Method (Continuous Story) can also improve the Achievement of Student Learning Outcomes in Social Studies Subjects in Class IX A Students of SMP Negeri 1 Sekaran 2018/2019 Academic Year.